The Attitude of Zuhud and Wara’ of Abu Dujanah as the Foundation for Building Muslim Integrity - Destia Muliana; Zaskia Nazwa; Dina Novita; Lia Fitriatul Arifah (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2026)
The erosion of moral integrity in contemporary Muslim societies, manifested in widespread corruption, materialism, and ethical misconduct, reflects an increasing gap between religious identity and lived ethical behavior. This article aims to reexamine the foundations of Islamic ethics by analyzing the spiritual attitudes of zuhud and wara’ as embodied in the life of Abū Dujānah Simāk ibn Kharasha al-Anṣārī, a distinguished Companion of the Prophet Muhammad ﷺ. Employing a qualitative descriptive design with a library research approach, this study draws on primary sources such as the Qur’an, authenticated Hadith collections, and classical biographical works, as well as secondary sources from contemporary academic scholarship on Islamic spirituality and Muslim integrity. Data were analyzed using content analysis and thematic analysis to explore the conceptual framework of zuhud and wara’, their manifestation in Abū Dujānah’s character, and their relevance for addressing modern ethical challenges. The findings indicate that zuhud functions as an inner motivational orientation that prioritizes eschatological accountability over worldly gain, while wara’ operates as a continuous moral vigilance that governs ethical behavior, particularly in situations of ambiguity and pressure. When integrated within the broader framework of taqwā, these two virtues form a robust spiritual foundation for authentic Muslim integrity. The study concludes that Abū Dujānah’s spiritual biography provides a historically grounded, theologically sound, and practically relevant ethical model, demonstrating that zuhud and wara’ are not merely historical ideals but living virtues capable of fostering moral resilience and integrity in contemporary Muslim societies.